The avant-garde searches in the national historical and literary process of 1960- 1980-s - Rosalia M. Svetlova3, Venera R. Amineva1 Leysan G. Ibragimova2 (Opción, 2019)
The aim of the study is to investigate the avant-garde searches inthe national historical and literary process of 1960-1980-s via thesystem-structural, comparative-typological and comparative researchmethods. As a result, the second direction of avant-garde searches isconnected with the use of different-stage figurative languages(mythopoetic, troped, simple word) within the same work, which entersinto dialogue with each other. It is concluded that the avantgardesearches of Yuzeev, R. Akhmetzyanov reflect the general patterns ofthe national historical and literary process and at the same time areassociated with the processes of national-cultural selfidentification ofindividual author's artistic systems.